Account Representative’s Challenges in Supervising Affiliated Transactions on Intragroup Loans (E-Jurnal Akuntansi, 2026)
Amendments to the supervisory business process by the Directorate General of Taxes in SE-05/PJ/2022 require the Account Representative to conduct transfer pricing analysis. The analysis at the supervision stage is expected to improve cooperative compliance and reduce transfer pricing disputes. This study will examine the problems in monitoring affiliate transactions on intragroup loans by Account Representatives as a result of business process changes. This study makes a empirical contribution by addressing research gap in affiliate transactions on intragroup loans from the standpoint of tax supervisions. This study is a case study on Account Representatives at the Directorate General of Taxes, conducted using qualitative descriptive methodologies. Open-ended surveys and interviews are utilized for triangulation purposes to increase the level of validity. The findings revealed that barriers to the supervision of affiliate transactions on intragroup loans include inadequate personnel capability, lack of taxpayer cooperation, regulatory issues and organizational issues.
Keywords: Account Representative; Affiliate Transaction; Cooperative Compliance; Intragroup Loan